Development of Phil-HEI and its evaluation of the Filipino diet: 2018 expanded national nutrition survey - Agdeppa, Imelda Angeles; Toledo, Marvin B; Dariagan, Janine Marie S; Zamora, Jezreel Ann T (World Nutrition Journal, 2024)
The Philippine Healthy Index (Phil-HEI) is a locally developed diet quality index. Patterned the American Healthy Eating Index (HEI), it aims to assess an individual’s diet quality through a scoring metric based on existing dietary guidelines.